2016
DOI: 10.7759/cureus.809
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of Medical Intensive Care Unit at Tertiary Care Hospital Setting of Pakistan

Abstract: Objective: To determine the frequency of micro-organisms causing sepsis as well as to determine the antibiotic susceptibility and resistance of microorganisms isolated in a medical intensive care unit.Materials and methods: This is a cross-sectional analysis of 802 patients from a medical intensive care unit (ICU) of Shifa International Hospital, Islamabad, Pakistan over a one-year period from August 2015 to August 2016. Specimens collected were from blood, urine, endotracheal secretions, catheter tips, tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 14 publications
8
24
1
Order By: Relevance
“…In our study, out of the total bacterial isolates, gram-negative bacteria were more prevalent than were gram-positive bacteria. This predominance of gram-negative bacteria is in concordance with the ndings of the similar study conducted (Qadeer et al 2016) [12] and result showed lower resistance in E. coli. According to Saravanan R. et al, 2013 [16] E. coli was found to be the most common and highly resistant organism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, out of the total bacterial isolates, gram-negative bacteria were more prevalent than were gram-positive bacteria. This predominance of gram-negative bacteria is in concordance with the ndings of the similar study conducted (Qadeer et al 2016) [12] and result showed lower resistance in E. coli. According to Saravanan R. et al, 2013 [16] E. coli was found to be the most common and highly resistant organism.…”
Section: Discussionsupporting
confidence: 92%
“…In gender wise distribution as 66.6% of total population was male and 33.3% of total population were female and similar study was conducted by Qadeer et al, 2016 [12] where 56.6% were males and 43.3% were female patient were found. Therefore, study data shows that the male was most exposed population to the antibiotic than female.…”
Section: Discussionsupporting
confidence: 75%
“…Esposito et al, in their study, also registered high resistance toward carbapenems [5]. Similar to our study, the most sensitivity is shown towards colistin by Qadeer and Rajan [6][7], whereas Ahmad and Esposito showed the highest sensitivity of tigecycline towards Acinetobacter. There has been a lot of concerns regarding the multidrug resistance toward Acinetobacter and its role in nosocomial infections.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Qadeer et al also showed 93% sensitivity toward amikacin and 90% towards carbapenems (meropenem and imipenem). But the most sensitivity in their study was shown toward colistin (100%) [7]. Ahmad et al also demonstrated high sensitivity towards amikacin (80%) and imipenem (100%) [8].…”
Section: Discussionmentioning
confidence: 78%
“…P. aeruginosa isolated from other body site infections often showed much higher resistance than eye isolates. In separate studies, isolates of P. aeruginosa from urinary tract infection, multiple body sites of intensive care unit patients and cystic fibrosis cases showed only 62, 41 and 44 per cent sensitivity to ciprofloxacin, respectively.…”
Section: P Aeruginosa In Eye Infectionsmentioning
confidence: 99%